Brachiosaurus : the largest dinosaur - Obiols, Anna, 1975- (Obiols, Anna, 1975- Dinosaur series., 2012)
"The little boy in this story has a very vivid imagination and a lot of interest in dinosaurs. In this whimsical tale, he makes friends with a Brachiosaurus. As the story progresses, he discovers facts about his dinosaur friend and learns how the Triceratops differs from all other dinosaurs. At the story's end, he wakes up in his bed, discovers that he'd been dreaming, and finds himself cuddling a stuffed toy dinosaur"--Cover, p. [4].